Don’t Drop Me Outside in 21st Century: A Cry from the Indus Valley Region - Shoro, Iram; Tagar, Hamzo Khan; Rubab, Rahila Khatoon; Naveed, Muhammad (Archives of Business Research, 2022)
Quality education for all is the 4th universal agenda of sustainable development goals is a comprehensive plan of United Nations Organizations (UNO), but still, millions of schools aged eligible children are out of school globally, particularly the majority of belongs to African and south Asian regions which demand us to analysis the situations and sort out the key challenges and policy flaws. There is a need of the hour to formulate robust policy documents and well-implementation strategies to save the future of tomorrow’s people in greater human development interest. Pakistan is dealing with this chronic problem and at least 22 million Pakistanis children are out of school in the 21st century. The qualitative analysis concludes that scarce allocation and its time-barred utilization system with massive mismanagement hampered the above-referred agenda of human development. The study finds that development allocation fared poorly; a lower literacy rate contributes to unskilled labor, spreading absolute poverty and inequality in the country. The identified social ills spread negative trends in a society like street crime, terrorism, and slow growth in the economy because of the out of school children. There is an urgent need to adopt inclusive development policies, practices, and strategies with a participatory approach to tackle the challenge in greater human development interest.